STUDY ON EARLY ISLAMIC ENGINEERING - Taqiyuddin Muhammad; Muhammad Faqih Nidzom; Hani'atul Mabruroh (Indonesian Journal of Islamic History and Culture, 2022)
Epistemologically, natural science occupies an important position in Islam. By studying them, the appreciation of the signs of Allah's creation becomes higher. On this basis, we find various names of Muslim scientists, especially engineering in Islam. The most important figures that we discuss this time, are not new names. At least, this figure is famous for his manuscripts that are still around today. In fact, they are proven to have inspired the emergence of various engineering sciences in the west. These figures have proved to be quite complex engineering on the engineering sciences of previous civilizations, including Greece, Egypt and Persia. Their work is a combination of Islamic appreciation of pre-Islamic civilization, along with the framework of Muslims at that time. This fact is not appreciated much except after the emergence of intensive studies on the history of science. Among the characters is Sabra, Sarton, to other historians of science. Some of them also translated the original work from Arabic. Some others make replicas of their findings. Among the most famous is the elephant clock. This article attempts to critically reveal matters related to the contributions of these three figures in Islamic engineering, as well as trace their general contribution to modern civilization.